Accelerated, free‐breathing, noncontrast, electrocardiograph‐triggered, thoracic MR angiography with stack‐of‐stars k‐space sampling and GRASP reconstruction. Issue 1 (5th September 2018) - Haji‐Valizadeh, Hassan; Collins, Jeremy D.; Aouad, Pascale J.; Serhal, Ali M.; Lindley, Marc D.; Pang, Jianing; Naresh, Nivedita K.; Carr, James C.; Kim, Daniel
Abstract : Purpose: To develop an accelerated, free‐breathing, noncontrast, electrocardiograph‐triggered, thoracic MR angiography (NC‐MRA) pulse sequence capable of achieving high spatial resolution at clinically acceptable scan time and test whether it produces clinically acceptable image quality in patients with suspected aortic disease. Methods: We modified a "coronary" MRA pulse sequence to use a stack‐of‐stars k‐space sampling pattern and combined it with golden‐angle radial sparse parallel (GRASP reconstruction to enable self‐navigation of respiratory motion and high data acceleration. The performance of the proposed NC‐MRA was evaluated in 13 patients, where clinical standard contrast‐enhanced MRA (CE‐MRA) was used as control. For visual analysis, two readers graded the conspicuity of vessel lumen, artifacts, and noise level on a 5‐point scale (overall score index = sum of three scores). The aortic diameters were measured at seven standardized locations. The mean visual scores, inter‐observer variability, and vessel diameters were compared using appropriate statistical tests. Results: The overall mean visual score index (12.1 ± 1.7 for CE‐MRA versus 12.1 ± 1.0 for NC‐MRA) scores were not significantly different ( P > 0.16). The two readers' scores were significantly different for CE‐MRA ( P = 0.01) but not for NC‐MRA ( P = 0.21). The mean vessel diameters were not significantly different, except at the proximal aortic arch ( P < 0.03). The mean diameters were strongly correlated (R 2 ≥ 0.96) and in good agreement (absolute mean difference ≤ 0.01 cm and 95% confidence interval ≤ 0.62 cm). Conclusion: This study shows that the proposed NC‐MRA produces clinically acceptable image quality in patients at high spatial resolution (1.5 mm × 1.5 mm × 1.5 mm) and clinically acceptable scan time ( 6 min).